2023
DOI: 10.1007/s10803-023-06159-4
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of Relative Clauses in Autism: The Role of Executive Functions and Language

Eleni Peristeri,
Xanthi Kamona,
Spyridoula Varlokosta

Abstract: Purpose Relative clauses present a well-known processing asymmetry between object-extracted and subject-extracted dependencies across both typical and atypical populations. The present study aimed at exploring the comprehension of object and subject relative clauses as conceptualized by the Relativized Minimality framework in autistic children and in a group of age- and IQ-matched typically-developing children. The study also explored the way performance in relative clauses would be affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…The frequent use of compound words in the texts has probably contributed to the fact that the particular test had a significant contribution to the children's reading comprehension performance. We should note that the performance of the group with ASD and low cognitive abilities in compound word production was lower than that of the children with intact cognitive skills, which agrees with many studies that have found morphosyntactic difficulties in children on the spectrum (Eigsti et al, 2007;Sukenik and Friedmann, 2018;Peristeri et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…The frequent use of compound words in the texts has probably contributed to the fact that the particular test had a significant contribution to the children's reading comprehension performance. We should note that the performance of the group with ASD and low cognitive abilities in compound word production was lower than that of the children with intact cognitive skills, which agrees with many studies that have found morphosyntactic difficulties in children on the spectrum (Eigsti et al, 2007;Sukenik and Friedmann, 2018;Peristeri et al, 2023).…”
Section: Discussionsupporting
confidence: 89%